Effect of turbidity on water disinfection by chlorination with the emphasis on humic acids and chalk. Issue 13 (7th June 2019) - Léziart, Tangui; Dutheil de la Rochere, Pierre-Marie; Cheswick, Ryan; Jarvis, Peter; Nocker, Andreas
ABSTRACT: Chlorine is globally the most widely used chemical for water disinfection. Whereas disinfection efficiency is well known to depend on water pH and temperature, the effect of turbidity is less well studied. Although turbidity is measured online in most drinking water works and most countries where regulations exist have set limits of <1 NTU for water leaving the works, the composition of turbidity is typically unknown. Given the heterogeneous nature of substances contributing to turbidity, the aim of this work was to study the effect of selected compounds on chlorination efficacy. The effect of humic acids and chalk on the inactivation of the indicator bacteria Escherichia coli and Enterococcus faecalis was assessed at neutral pH at different turbidity levels using both plate counting and flow cytometry in combination with membrane integrity staining. For humic acids, a turbidity of 1 NTU (corresponding to 2 mg L −1 ) was identified as a critical threshold, which when exceeded was found to have a negative impact on chlorine disinfection. Chalk, on the other hand, had no measurable impact up to 5 NTU. The observation applied to both bacterial species with identical conclusions from the two diagnostic methods. Results corroborate that different turbidity causing substances affect chlorination efficiency to very different extents with chlorine demand by organic material probably being the most important determinant. In the case of turbidities >1 NTU, turbidity measurement benefits from the consideration of the organic content as mere NTU values do not allow predicting an impact on chlorination efficiency. GRAPHICAL ABSTRACT: